Functional Characterization of Pomegranate CAMTA3 in Cold Stress Responses - Shuangshuang Zhao; Rui Lu; Lijuan Feng; Mengyu Zheng; Han Zhang; Yanlei Yin; Ling Zheng (Plants)
Cold stress is a significant factor limiting plant growth and development. Pomegranate is particularly susceptible to low temperatures. Calmodulin-binding transcriptional activators (CAMTAs) are key regulators of cold stress tolerance in plants. In this study, we conducted a comprehensive analysis of the CAMTA family proteins across 12 species, including Punica granatum (pomegranate), using bioinformatic methods. Pomegranate CAMTA3 (PgCAMTA3) was isolated and characterized, and it demonstrated enhanced cold tolerance when expressed in Arabidopsis thaliana. Quantitative real-time PCR (qRT-PCR) analysis showed that the expression of PgCAMTA3 was up-regulated under cold and ABA treatments in pomegranates. Two A. thaliana transgenic lines, OE1 and OE2, which overexpress PgCAMTA3, were generated through genetic transformation. The overexpression of PgCAMTA3 enhanced the cold stress tolerance in transgenic A. thaliana. OE1 and OE2 exhibited higher survival rates under cold stress. Furthermore, enzymatic activity assays revealed enhanced peroxidase (POD), catalase (CAT), and superoxide dismutase (SOD) in OE lines. These antioxidant enzymatic activities collectively contribute to better cold stress tolerance by providing more effective reactive oxygen species (ROS) scavenging and cellular protection mechanisms, which was confirmed by lower levels of malondialdehyde (MDA) and ROS production. In addition, the overexpression of PgCAMTA3 led to the upregulation of the expression levels of AtCBF2, AtNCED3, and AtWRKY22, which were modulated by CAMTA3. In summary, we report the significant role of PgCAMTA3 in plant cold tolerance. Our findings provide valuable insights into the CAMATA family in plants and offer new perspectives on the molecular mechanisms underlying cold tolerance in pomegranates.